Anemia among children and adolescents in a rural area - Ivan Riyanto Widjaja; Felix Firyanto Widjaja; Lucyana Alim Santoso; Erick Wonggokusuma; Oktaviati Oktaviati (Indonesian Pediatric Society Publishing House, 2014)
Background Anemia in children and adolescents affects growth and development. It is a preventable disease, but unfortunately is often ignored until the symptoms occur. There have been limited reports on the prevalence of anemia in children and adolescents in Indonesia, especially from rural areas. Objective To describe the prevalence of anemia in children and adolescents in district ofMalinau, a rural area in East Kalimantan Province. Methods This cross-sectional study was done in June 20 10 using laboratory records between July 2009 to January 20 10. Laboratory records of patients aged between 6 months and 18 years which investigated were complete blood count (CBC) from ambulatory, inpatient, and emergency care ofMalinau Public Hospital in East Kalimantan. Mentzer and England & Fraser indices were used to differentiate iron deficiency anemia (IDA) and thalassemia among microcytic hypochromic anemic patients. Results This study involved 709 laboratory records. Prevalence of anemia was 53 .9% (95% CI 50.2% to 57 .5%) . The prevalence of IDA among age groups were as follows: 29.4% (95% CI 24.3 to 34.5%) in 6- 59 months group, 16% (95% CI 11 to 21 %) in 5- 11.9 years, and 15.2% (95% CI 10.2 to 20.2%) in 12- 18 years. Children aged 6- 59 months tended to have more anemia th an those aged 5- 11.9 years (OR 2. 184, 95% CI 1.398 to 3.413) or aged 12- 18 years (OR 2.3 19, 95% CI 1.464 to 3.674). Conclusion T he prevalence of an emia in children and adolescents of the Malinau Regency is 53 .9% (95% CI 50.2 to 57.5%), quite similar to that of other developing countries . A government program to overcome anemia is recommended, n ot only for pregnant women, but also for children and adolescents.